Analisa Yesaya 53: Nubuatan tentang Mesias atau Penggambaran tentang Israel - Refamati Gulo (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2024)
Jewish rabbis after the fall of Jerusalem were more inclined to interpret the suffering servant in Isaiah 53 as the nation of Israel. As for the Jewish rabbis who stated that Isaiah 53 prophesied the nation of Israel as the suffering servant and stated that the prophecy had been fulfilled, where the nation of Israel suffered under other nations because they rejected Jesus as the Messiah. This study aims to investigate and analyze Isaiah 53, focusing on the question of whether the prophecy is more appropriately interpreted as a description of the Messiah or as a description of Israel by using the descriptive method of analysis. The results show that the prophecy consistently describes the characteristics of the Messiah, identifying specific elements that support this interpretation. Although there is an alternative view that views Isaiah 53 as a description of Israel's fate, this argument seems less consistent with aspects of the text and context. This study can provide in-depth insights into the meaning and interpretation of Isaiah 53, resulting in a significant contribution to biblical studies, as well as unearthing theological and spiritual implications that can enrich our understanding of this prophetic message.